2017
DOI: 10.1039/c6ob02285e
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctionalized strategy of indoles to C2-quaternary indolin-3-ones via a TEMPO/Pd-catalyzed cascade process

Abstract: A method for combinative oxidative homo dimerization and cyanomethylation of free indole derivatives catalysed by TEMPO and Pd(OAc) was demonstrated for the first time. This new methodology is both atom and step efficient and is applicable to a broad scope of substrates, allowing the synthesis of a range of synthetically valuable 2-(2-(1H-indol-3-yl)-3-oxoindolin-2-yl)acetonitriles in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Notably, decreasing the amount of Cu(OTf)2 to 0.005 equivalent had no effect on the reactivity of the reaction (Table 1, entry 10). Moreover, under the optimized conditions, the dimer 6a was obtained in 98% reactions focus on the construction of di-or trimerization of indoles [50,[77][78][79][80], and the reactions of indoles with dissimilar C-H nucleophiles are considerably rare [81][82][83]. Recently, we reported an efficient oxidative dearomatization reaction of indoles [84,85].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, decreasing the amount of Cu(OTf)2 to 0.005 equivalent had no effect on the reactivity of the reaction (Table 1, entry 10). Moreover, under the optimized conditions, the dimer 6a was obtained in 98% reactions focus on the construction of di-or trimerization of indoles [50,[77][78][79][80], and the reactions of indoles with dissimilar C-H nucleophiles are considerably rare [81][82][83]. Recently, we reported an efficient oxidative dearomatization reaction of indoles [84,85].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, Liu et al revealed that acetonitrile was smoothly coupled via a TEMPO/Pdcatalyzed cascade process. [123] Notably, halogen functionalities including fluoro, chloro, and bromo were compatible with this palladium catalysis. The same group also explored TMSCN as a cyanating reagent for the similar cascade oxygenation, in which a palladium-free catalytic system was found to be effective (Scheme 54).…”
Section: Indole Oxygenationmentioning
confidence: 93%
“…Indolin‐3‐ones are versatile synthetic building blocks and utilizedas core structures in thepreparation of various naturalproducts, such as austamide, halichrome A , cephalinone, andfluorocurine . Especially, polyfunctional indolidin‐3‐ones areof considerable useful intermediates for the construction of natural products…”
Section: Methodsmentioning
confidence: 99%